The Japanese family storehouse : - Ihara, Saikaku (University Press, 1969)
My aim in producing this study and tranlation of Saikaku's Nippon Eitai-gura has been to give a reasonably accurate impression of a single work of Japanese literature, presenting it in the context of the society and literature of it age.